Eleven years secular trend of the initiation of anti-osteoporosis medications and subsequent fractures in Taiwan: From 2008 to 2018 - Tsung-Han Yang; Chen-Yu Wang; Shau-Huai Fu; Ding-Cheng Chan; Ho-Min Chen; Jou-Wei Lin; Chun-Feng Huang; Jen-Jia Yang; Chih-Hsing Wu; Jawl-Shan Hwang; Rong-Sen Yang (Journal of the Formosan Medical Association, 2023)
Background: Osteoporosis is a common metabolic bone disease that benefits from many newly developed anti-osteoporosis medications (AOMs). Reimbursement policies need to allocate medical budgets properly based on evidence-based data. This study aimed to investigate the 11-year secular trend, focusing on older age and males in this adjustment wave of the National Health Insurance reimbursement. Methods: We adopted a nationwide cohort from Taiwan's National Health Insurance Research Database (NHIRD). Patients undergoing newly initiated AOMs from 2008 to 2018 were included. The AOMs in this study included denosumab, zoledronate, ibandronate, alendronate, raloxifene, and risedronate. Patients <50 years, pathological fractures, missing data, and two AOMs prescribed were excluded. The real-world trends related to subsequent fragility fracture and death within 1 and 3 years were used to evaluate the potential effects due to revision of reimbursement policies. Results: Of 393,092 patients, among them, 336,229 patients met the criteria, whose mean age ranged from 73.3 to 74.4 years, and nearly 80% were female. Further analysis showed a steady increase of AOMs from 5567 (17.1%) and 8802 (27.0%) in 2008–6697 (18.3%) and 10,793 (29.5%) in 2018 for males and 80+ years respectively. The subsequent fragility fracture within one and three years post AOMs initiation was 5.81% and 11.80% in 2018. Conclusion: This study showed an immediate drop in AOMs prescription after the implementation of a new stricter reimbursement policy. It took 5 years to return the annual prescription number.